Cross-modality translations improve recognition by reducing false alarms - Forrin, Noah D.; MacLeod, Colin M. (Memory (Hove), 2018)
Conway and Gathercole [(1990). Writing and long-term memory: Evidence for a "translation" hypothesis. The Quarterly Journal of Experimental Psychology, 42, 513-527] proposed a translation account to explain why certain types of encoding produce benefits in memory: Switching modalities from what is presented to what is encoded enhances item distinctiveness. We investigated this hypothesis in a recognition experiment in which the presentation modality of a study list (visual vs. auditory) and the encoding activity (speaking vs. typing vs. passive encoding) were manipulated between-subjects. Manipulating encoding activity between-subjects ruled out any potential influence of the relationally distinct processing that can occur in a within-subject manipulation (in which all previous translation effects have been demonstrated). We found no overall difference in memory for words presented auditorily vs. visually nor for visual vs. auditory encoding, but critically presentation modality and encoding activity did interact. Translating from one modality to another - particularly from auditory presentation to visual encoding (typing) - led to the best memory discrimination. This was largely because of reduced false alarms, not increased hits, consistent with the distinctiveness heuristic.